Channel Characteristics of High-Speed Railway Station Based on Ray-Tracing Simulation at 5G mmWave Band - Lei Xiong; Haiyang Miao; Bo Ai; Tutun Juhana; Adit Kurniawan (International Journal of Antennas and Propagation)
In order to satisfy the increasing demand for the higher transmission capacity of “smart station”, millimeter wave (mmWave) technology is expected to play a significant role in the high data rate communication system. Based on the ray-tracing simulation technology, this paper would study wireless channel characteristics of the three-dimensional (3D) model of high-speed railway station at the mmWave band. Key parameters such as path loss exponent, shadow fading factor, delay spread, Rician K-factor, angular spread, power angle spectrum, and spatial correlation are extracted and investigated. These channel characteristics are of value for the selection of antenna arrays and even the design of future 5G communication networks in the railway environment.